Mathematical modeling of the reactive modification of high-density polyethylene. Effect of vinyl content - Brandolin, Adriana (2007)
Molecular properties of high-density polyethylene resulting after its peroxide modification process depend not only on peroxide concentration and temperature but also on the molecular weight distribution and vinyl content of the virgin resin. A model able to predict average molecular weights and vinyl content changes after treatment with different peroxide concentrations is presented in this work. The model is able to handle virgin resins with or without vinyl content. For that purpose, a kinetic mechanism is proposed that includes the reactions of termination with initiation radicals and polymer double-bond propagation besides other commonly accepted reactions. Average molecular weights and vinyl content were calculated after solving the mass balance equations. These were previously bounded by applying a double moment technique. Molecular weights and vinyl content predictions compare well with experimental data. A deeper insight into the influence of initial vinyl content on the evolution of molecular weights is obtained through model calculations.